PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) MELALUI EDUKASI CUCI TANGAN PADA ANAK PRA SEKOLAH DI TK AL HAFIZ, DESA MALAKA, KABUPATEN LOMBOK UTARA - Al Hafiez Ariouso; Rafi Radityo Daniswara; I Putu Reza Wedangga; Putu Arta Wibawa; Keisya Sherani Attari Yasmin; Mufidah Radwah Ja'faruddin; Indri Tiffani; Alfira Savitri; Alfiya Qurrata Aini; Sheilla Ninditya (Universitas Mataram, 2026)
Clean and Healthy Living Behavior (PHBS) in early childhood is an important effort to prevent the transmission of infectious diseases such as diarrhea and acute respiratory infections (ARI); however, handwashing practices among preschool children in Indonesia remain suboptimal, highlighting the need for early education using interactive, practice-based approaches involving teachers and the school environment. Various studies have shown that handwashing education interventions in educational settings are effective in improving children's knowledge, skills, and compliance. This community service activity aimed to improve the knowledge and skills of preschool children in applying proper handwashing techniques through interactive education at TK Al Hafiz, Malaka Village, North Lombok Regency. The activity employed an educational socialization method through counseling on sanitation, hygiene, and PHBS, conducted on August 13, 2025, involving 20 students and medical students from the Faculty of Medicine and Health Sciences, Universitas Mataram, as facilitators. The implementation included material delivery and direct practice of the six-step handwashing technique, while evaluation was conducted through observation of the children’s abilities. The results showed an improvement in the accuracy and independence of children in performing handwashing steps, accompanied by high enthusiasm during the activity and support from teachers and parents in sustaining the behavior. PHBS education through handwashing training has proven effective in improving children's knowledge and skills, making it an important promotive and preventive approach in establishing healthy behaviors from an early age.